TEACHING ALGEBRA THROUGH GAMES: A LITERATURE REVIEW - Valeria Yekti Kwasaning Gusti (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2025)
This systematic literature review investigates the application of game-based learning (GBL) in teaching algebra at the junior and senior secondary levels within the Indonesian education system between 2014 and 2024. The review synthesizes empirical studies written in both English and Indonesian, examining how digital and non-digital games have been used to support students' conceptual understanding, engagement, and problem-solving abilities in algebra. Out of an initial pool of approximately 3,000 studies, only 22 met the rigorous inclusion criteria, which focused on curriculum alignment, empirical design, measurable outcomes, and educational level. This selective scope ensures a focused and quality-driven synthesis of evidence relevant to the Indonesian context. Findings suggest that both digital platforms (e.g., Quizizz, Android-based games) and non-digital games (e.g., algebra-themed dominoes, board games) contribute positively to learning outcomes such as increased motivation, active participation, and deeper understanding of algebraic concepts. Game-based learning theory frequently underpins these interventions, highlighting the role of engagement and motivation in mathematical learning. Despite promising results, research gaps remain—particularly in the coverage of diverse algebraic topics and the long-term effectiveness of GBL approaches. This review underscores the potential of game-based strategies to enhance algebra instruction in Indonesia, while calling for broader and more methodologically diverse research in the future.